Method for preparing oxide composite insulating layer on surface of titanium alloy
By preparing an oxide composite insulating layer on the surface of the titanium alloy, the problem of waste of precious metals and easy damage during the electroplating process of titanium alloy hangers is solved, and good insulation effect and acid corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411879765.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-19
AI Technical Summary
During the electroplating process, titanium alloy hangers are likely to cause precious metals to be deposited on the non-working surface, resulting in waste of electroplating solution, and the titanium alloy is conductive and easy to be damaged.
The oxide composite insulating layer was prepared on the surface of the titanium alloy, and the porous titanium oxide layer was obtained by high-temperature oxidation, and then the pore sealing treatment was performed using organic pore sealing agent and ultrasonic treatment technology to form a stable oxide composite insulating layer.
It realizes the insulation effect of the surface of titanium alloy, resists strong acid corrosion, reduces the waste of electroplating solution, and improves the service life of titanium alloy hangers.
Smart Images

Figure CN119753561A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of insulating material preparation, in particular to a method for preparing an oxide composite insulating layer on the surface of a titanium alloy. Background Art
[0002] Electroplating of gold, nickel, etc. has been widely used in high-end watch and clock industries, and has been highly praised by users. At present, the gold-plated and nickel-plated hangers on the market mostly use TC4 titanium alloy hangers. Titanium alloy hangers usually need to be treated with strong acids such as hydrochloric acid and nitric acid to remove impurities, which makes the hangers easy to damage. In addition, titanium alloy hangers are conductive, and a certain thickness of precious metals such as gold and nickel are deposited on the non-working surface of the hanger during electroplating, resulting in a large amount of waste of electroplating solution. Therefore, how to insulate the non-working surface of the electroplating hanger surface has become a difficulty currently faced by the electroplating industry. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing an oxide composite insulating layer on the surface of a titanium alloy to solve the problems existing in the above-mentioned prior art.
[0004] To achieve the above object, the present invention provides the following solutions:
[0005] The present invention provides a method for preparing an oxide composite insulating layer on the surface of a titanium alloy, comprising the following steps:
[0006] (1) oxidizing the deoiled and degreased titanium alloy at 750-900° C. for 5-10 hours, and then cooling the alloy to room temperature in the furnace to obtain a porous titanium oxide layer on the surface of the titanium alloy;
[0007] (2) placing the titanium alloy having a porous titanium oxide layer on the surface obtained in step (1) in an organic sealing agent solution, performing ultrasonic treatment, drying, and repeating the ultrasonic treatment process 5-10 times;
[0008] (3) curing the material treated in step (2) at 120-500° C. for 1-5 hours to prepare an oxide composite insulating layer on the surface of the titanium alloy;
[0009] The organic sealing agent solution is obtained by mixing the organic sealing agent and water in a volume ratio of 1:5-1:9, more preferably in a volume ratio of 1:9.
[0010] Furthermore, the organic sealing agent may be a commercial silane or polyurethane sealing agent.
[0011] Furthermore, step (1) is oxidized at 700° C. for 7 h.
[0012] Furthermore, the power of the ultrasonic treatment in step (2) is 1 to 20 kW, and the time is 30 to 60 min; the number of ultrasonic treatments in step (2) is 8 times.
[0013] Furthermore, step (3) is cured at 150° C. for 2 h.
[0014] Furthermore, the thickness of the porous titanium oxide layer is 50-120 μm; the thickness of the organic sealing layer is 10-50 μm.
[0015] The porous titanium oxide layer and the organic sealing layer are both insulating materials and are resistant to strong acid corrosion. The key technical point is how to make the organic sealing agent penetrate into the porous structure. To solve this problem, the present invention obtains an ideal sealing result through a composite process of diluting the sealing agent + ultrasonic assistance + multiple sealing.
[0016] The present invention also provides the titanium alloy having an oxide composite insulating layer on the surface, which is prepared by the above preparation method.
[0017] The present invention further provides the use of the titanium alloy having an oxide composite insulating layer on the surface as a watch hanger.
[0018] At present, the influence of existing thermal spraying, micro-arc oxidation and sealing treatment composite technology on the performance of titanium alloy hangers is still unknown. The preliminary research of the present invention found that the thermal spraying and sealing composite process has high manufacturing cost, and the sprayed oxide layer has poor bonding with the substrate. During use, the strong acid corrodes the interface, causing the coating to peel off after 8 electroplating times. In addition, the insulation effect of the sprayed coating after sealing treatment is poor; the composite process of micro-arc oxidation and sealing treatment is unstable, the oxide layer thickness is uneven, and the insulation effect is poor.
[0019] The present invention discloses the following technical effects:
[0020] The present invention provides a method for preparing an oxide composite insulating layer on the surface of a titanium alloy, wherein the oxide composite insulating layer is composed of a subsurface porous titanium oxide layer and a surface organic sealing layer; the present invention performs high-temperature oxidation on the titanium alloy in an atmospheric environment to obtain the porous titanium oxide layer, then uses an organic sealing agent to perform ultrasonic-assisted sealing treatment on the porous structure, and obtains the oxide composite insulating layer after curing treatment.
[0021] The oxide composite insulating layer prepared on the surface of the titanium alloy has good insulating ability in a solution environment and is resistant to corrosion by hydrochloric acid and nitric acid, and has good application in gold-plated and nickel-plated hangers in the watch industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a graph showing the bonding strength test of the oxide composite insulating layer in Example 1 of the present invention;
[0024] Figure 2 This is a surface SEM morphology image of the oxide composite insulating layer in Example 1 of the present invention;
[0025] Figure 3 is a cross-sectional SEM image of the oxide composite insulating layer in Example 4 of the present invention;
[0026] Figure 4 This is a graph showing the bonding strength test of the oxide composite insulating layer in Example 4 of the present invention;
[0027] Figure 5 This is the SEM morphology of the oxide layer surface in Comparative Example 1;
[0028] Figure 6 This is a test diagram of the bonding strength of the oxide layer in Comparative Example 6. DETAILED DESCRIPTION
[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0030] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] In the following examples and comparative examples of the present invention, the ratio of the organic sealing agent to water is a volume ratio.
[0035] Example 1
[0036] Method for preparing oxide composite insulating layer on titanium alloy surface:
[0037] S1: The titanium alloy is subjected to ultrasonic degreasing and degreasing treatment, and then dried;
[0038] S2: Place the dried titanium alloy into a furnace and oxidize it in an atmospheric environment. The oxidation process parameters are: oxidation temperature 750°C, holding time 7h; cool to room temperature with the furnace to obtain a titanium alloy sample with a porous titanium oxide layer on the surface; wherein the thickness of the porous titanium oxide layer is 104.3μm.
[0039] S3: Mix the polyurethane sealer and water in a ratio of 1:9 (also called diluent) and place it in an ultrasonic device, and place the titanium alloy sample with a porous titanium oxide layer on the surface into the diluent, perform ultrasonic penetration treatment at 20kW for 30 minutes, then take it out and air dry it, and repeat the above operation 8 times;
[0040] S4: The titanium alloy sample with a porous titanium oxide layer on the surface after the sealing treatment is placed in a furnace for curing treatment at a drying temperature of 150°C for 2 hours to obtain a sealing layer with a thickness of 28 μm, and finally a titanium alloy with an oxide composite insulating layer on the surface is obtained.
[0041] The Rockwell indentation method is used to test the bonding strength of the porous titanium oxide layer. The test load is 60kg. The bonding strength test standard refers to the international ISO 26443:2008; GB / T 1.1-2009. The coating bonding strength is defined as HF1 to HF6, where the smaller the grade, the higher the bonding strength. Coatings with HF and HF2 bonding strengths can meet industrial applications.
[0042] Insulation performance test: Use a 15*15*5 test piece as the cathode for electroplating, then place it in a nickel plating solution for electroplating for 1 hour, then take it out and see the proportion of the nickel plating layer occupying the surface area of the coating to determine the insulation of the oxide insulating layer. Among them, the surface of the test piece is completely covered with nickel, indicating poor insulation; the surface of the test piece does not contain a nickel plating layer, indicating insulation. According to industrial application requirements, an insulating oxide composite layer can meet industrial needs.
[0043] HCl corrosion resistance: Use an electrochemical workstation to test the corrosion potential of the test piece in a 10 vol.% solution. The smaller the corrosion potential value, the worse the corrosion resistance.
[0044] Embodiment 2-6
[0045] Examples 2-6 provide porous titanium oxide layers and organic sealing layers with different thicknesses.
[0046] The specific parameters of each step of Examples 2-6 are shown in Tables 1-4:
[0047] S1. Same as Example 1;
[0048] S2. Adjust the oxidation process parameters to prepare oxide layers of different thicknesses, as shown in Table 1:
[0049] Table 1
[0050]
[0051] S3. Adjust the process parameters such as the ratio of sealing agent to water and the number of sealing times, as shown in Table 2:
[0052] Table 2
[0053]
[0054] S4. The titanium alloy sample having a porous titanium oxide layer on the surface after the sealing treatment is cured to obtain a composite insulating layer, and the adjustment parameters include the curing temperature and the holding time, as shown in Table 3:
[0055] Table 3
[0056]
[0057]
[0058] Comparative Example 1
[0059] The only difference from Embodiment 1 is that step S3 and step S4 are not performed.
[0060] Comparative Example 2
[0061] The only difference from Example 1 is that the temperature of step S2 is adjusted to 710° C. and the time is adjusted to 11 h.
[0062] Comparative Example 3
[0063] The only difference from Example 1 is that the temperature of step S2 is adjusted to 910° C. and the time is adjusted to 4 hours.
[0064] Comparative Example 4
[0065] The only difference from Example 1 is that the ratio of the organic sealing agent to water in step S3 is adjusted to 1:4, and the number of sealing times is adjusted to 4 times.
[0066] Comparative Example 5
[0067] The only difference from Example 1 is that the ratio of the organic sealing agent to water in step S3 is adjusted to 1:11, and the number of sealing times is adjusted to 11 times.
[0068] Comparative Example 6
[0069] The only difference from Example 1 is that the furnace cooling in step S2 is adjusted to air cooling.
[0070] Comparative Example 7
[0071] The only difference from Example 1 is that the ultrasonic osmosis treatment in step S3 is not performed.
[0072] Comparative Example 8
[0073] The only difference from Embodiment 1 is that step S4 is not performed.
[0074] Comparative Example 9
[0075] The only difference from Example 1 is that the temperature in step S4 is adjusted to 110° C. and the time is adjusted to 5 hours.
[0076] Comparative Example 10
[0077] The only difference from Example 1 is that the temperature in step S4 is adjusted to 210°C.
[0078] Comparative Example 11
[0079] The only difference from Example 1 is that the porous titanium oxide layer in step S2 is replaced by ZrO2 of the same thickness sprayed by plasma.
[0080] Comparative Example 12
[0081] The only difference from Example 1 is that the porous titanium oxide layer in step S2 is replaced by an oxide layer of the same thickness prepared by a micro-arc oxidation process.
[0082] The test results of the oxide composite insulating layer on the surface of the titanium alloy samples of Examples 1-6 are shown in Table 4:
[0083] Table 4
[0084]
[0085] The test results of the insulation layer performance on the surface of the titanium alloy samples of Example 1 and Comparative Examples 1-12 are shown in Table 5:
[0086] Table 5
[0087]
[0088] The test method for the bonding strength of the oxide composite insulating layer is the same as the test method for the bonding strength of the porous titanium oxide layer.
[0089] It can be seen from Table 4 and Table 5 that the oxide composite insulating layers prepared in Examples 1-6 of the present invention have high bonding strength, corrosion resistance and insulating properties, and can meet the needs of industrial production.
[0090] In comparison, the porous titanium oxide layer without sealing treatment (Comparative Example 1) has poor insulation and corrosion resistance and cannot meet production requirements; the coating that is air-cooled in step S2 (Comparative Example 6) or without ultrasonic assistance (Comparative Example 7) has poor corrosion resistance and insulation effects; the process parameters in S2, S3 and S4 are not within the requirements of the present invention, and it is difficult to achieve the requirements of insulation, corrosion resistance and high bonding strength; the coating using plasma spraying or micro-arc oxidation + sealing composite technology has poor protection effect.
[0091] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing an oxide composite insulating layer on a titanium alloy surface, characterized in that: The following steps are involved: (1) oxidizing the deoiled and degreased titanium alloy at 750-900° C. for 5-10 hours, and then cooling the alloy to room temperature in the furnace to obtain a porous titanium oxide layer on the surface of the titanium alloy; (2) placing the titanium alloy having a porous titanium oxide layer on the surface obtained in step (1) in an organic sealing agent solution, performing ultrasonic treatment, drying, and repeating the ultrasonic treatment process 5-10 times; (3) curing the material treated in step (2) at 120-500° C. for 1-5 h to obtain an organic sealing layer on the surface of the porous titanium oxide layer, thereby preparing an oxide composite insulating layer on the surface of the titanium alloy; The organic sealing agent solution is obtained by mixing an organic sealing agent and water in a volume ratio of 1:5-1:
9.
2. The method according to claim 1, characterized in that The organic sealing agent includes a silane sealing agent or a polyurethane sealing agent.
3. The method according to claim 1, characterized in that Step (1) is oxidized at 700°C for 7h.
4. The method according to claim 1, characterized in that: The power of the ultrasonic treatment in step (2) is 1 to 20 kW, and the time is 30 to 60 minutes.
5. The method according to claim 1, characterized in that The number of ultrasonic treatments in step (2) is 8 times.
6. The method according to claim 1, characterized in that Step (3) is to cure at 150°C for 2h.
7. The method according to claim 1, characterized in that The thickness of the porous titanium oxide layer is 50-120 μm; the thickness of the organic sealing layer is 10-50 μm.
8. A titanium alloy having an oxide composite insulating layer on its surface, characterized in that: The preparation method is adopted according to any one of claims 1 to 7.
9. Use of the titanium alloy having an oxide composite insulating layer on the surface as claimed in claim 8 as a watch hanger.
Citation Information
Patent Citations
High-temperature insulating inorganic hole sealant for thermal spraying ceramic coating and use method of high-temperature insulating inorganic hole sealant
CN104649713A
Preparation method of aluminum alloy petroleum drilling pipe threaded joint with insulation and wear-resistant corrosion resistance
CN108286065A
Preparation method of titanium alloy surface insulation hardened film layer and titanium alloy
CN115710685A